Lying, deception, equivocation and the ethics of prescribing placebos in clinical practice - Annoni, Marco (Rivista Italiana di Filosofia del Linguaggio, 1970)
In this paper I explore different ways in which doctors can be dishonest in clinical communications. As a case in point, I object to the idea that doctors can prescribe placebos in ways that are not transparent and yet not paternalistic. First, I briefly present evidence demonstrating that placebo effects may modulate a host of clinical outcomes. Second, I argue that doctor’s duty of truth-telling in clinical contexts entails two complementary obligations: the one not to lie and deceive (i.e, the duty of truthfulness), and the one to inform patients in order to respect their autonomy (i.e, the duty to inform). Third, I distinguish different ways in which doctors may violate their duty of veracity. Specifically, I identify two ways in which doctors may fail to uphold the duty of truthfulness (by lying and deceiving), and two ways in which they can instead infringe on the duty to inform (by keeping patients in the dark and by telling half-truths). Based on these distinctions, I conclude that doctors cannot have the placebo cake and eat it too: either they prescribe placebos in a fully transparent manner, or they need to morally justify a paternalistic exception to their duty of veracity